Dairy Tool Box Talks: A Comprehensive Worker Training in Dairy Farming - Rovai, Maristela; Carroll, Heidi; Foos, Rebecca; Erickson, Tracey; Garcia, Alvaro (Frontiers in Public Health, 2016)
Today’s dairies are growing rapidly, with increasing dependence on Latino immigrant workers. This requires new educational strategies for improving milk quality and introduction to state-of-the-art dairy farming practices. It also creates knowledge gaps pertaining to the health of animals and workers, mainly due to lack of time and language barriers. Owners, managers and herdsmen assign training duties to more experienced employees, which may not promote ‘best practices’ and may perpetuate bad habits. A comprehensive and periodic training program administered by qualified personnel is currently needed and will enhance the sustainability of the dairy industry. Strategic management and employee satisfaction will be achieved through proper training in the employee’s language, typically Spanish. The training needs to address not only current industry standards but also social and cultural differences. An innovative training course was developed following the same structure used by the engineering and construction industries, giving farm workers basic understanding of animal care and handling, cow comfort and personal safety. The “Dairy Tool Box Talks” program was conducted over a ten week period with nine 30-minute sessions according to farm’s various employee work shifts. Bulk milk bacterial counts and somatic cell count were used to evaluate milk quality on the three dairy farms participating in the program. “Dairy Tool Box Talks” resulted in a general sense of employee satisfaction, significant learning outcomes, and enthusiasm about the topics covered. We conclude this article by highlighting the importance of educational programs aimed at improving overall cross-cultural training.